Electrical conductivity and electrical modulus properties of ?, ?-dihexylsexithlophene organic semiconductor - Yakuphanoğlu, Fahrettin (Elsevier, 2007)
Electrical conductivity and dielectrical properties of alpha, omega-dihexylsexithiophene organic compound have been investigated by impedance spectroscopy. Direct current conductivity results confirm that alpha, omega-dihexylsexithiophene is an organic semiconductor with the calculated electronic parameters. Alternating current conductivity results Suggest that classical barrier hopping mechanism is dominant in alpha, omega-dihexylsexithiophene sample. The imaginary M '' part of electrical modulus shows an asymmetric peak, suggesting a temperature-dependent non-Debye relaxation. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: organic semiconductor; impedance spectroscopy; electrical modulus